What school-level and area-level factors influenced HPV and MenACWY vaccine coverage in England in 2016/2017? An ecological study. Issue 7 (11th July 2019) - Tiley, Karen; White, Joanne; Andrews, Nick; Tessier, Elise; Ramsay, Mary; Edelstein, Michael
Abstract : Objective: To describe school-level and area-level factors that influence coverage of the school-delivered human papillomavirus (HPV) and meningococcal A, C, W and Y (MenACWY) programmes among adolescents. Design: Ecological study. Setting and participants: Aggregated 2016/2017 data from year 9 pupils were received from 1407 schools for HPV and 1432 schools for MenACWY. The unit of analysis was the school. Primary and secondary outcome measures: Outcome measures were percentage point (pp) difference in vaccine coverage by schools' religious affiliation, school type, urban/rural, single sex/mixed and region. A subanalysis of mixed-sex, state-funded secondary schools also included deprivation, proportion of population from black and ethnic minorities, and school size. Results: Muslim and Jewish schools had significantly lower coverage than schools of no religious character for HPV (24.0 (95% CI −38.2 to −9.8) and 20.5 (95% CI −30.7 to −10.4) pp lower, respectively) but not for MenACWY. Independent, special schools and pupil referral units had increasingly lower vaccine coverage compared with state-funded secondary schools for both HPV and MenACWY. For both vaccines, coverage was 2 pp higher in rural schools than in urban schools and lowest in London. Compared with mixed schools, HPV coverage was higher in male-only (3.7 pp, 95% CI 0.2 to 7.2) and female-only (4.8 pp, 95% CI 2 to 7.6) schools. In the subanalysis, schools located in least deprived areas had the highest coverage for both vaccines (3.8 (95% CI 0.9 to 6.8) and 10.4 (95% CI 7.0 to 13.8) pp for HPV and MenACWY, respectively), and the smallest schools had the lowest coverage (−10.4 (95% CI −14.1 to −6.8) and −7.9 (95% CI −12 to −3.8) for HPV and MenACWY, respectively). Conclusions: Tailored approaches are required to improve HPV vaccine coverage in Muslim and Jewish schools. In addition, better ways of reaching pupils in smaller specialist schools are needed.